Cationic surfactant mediated fibrillogenesis in bovine liver catalase: a biophysical approach. Issue 10 (27th July 2018) - Khan, Mohsin Vahid; Zaman, Masihuz; Chandel, Tajalli Ilm; Siddiqui, Mohammad Khursheed; Ajmal, Mohd. Rehan; Abdelhameed, Ali Saber; Khan, Rizwan Hasan
Abstract : Protein aggregation into oligomers and mature fibrils are associated with more than 20 diseases in humans. The interactions between cationic surfactants dodecyltrimethylammonium bromide (DTAB) and tetradecyltrimethylammonium bromide (TTAB) with varying alkyl chain lengths and bovine liver catalase (BLC) were examined by various biophysical approaches. The delicate coordination of electrostatic and hydrophobic interactions with protein, play imperative role in aggregation. In this article, we have reconnoitered the relation between charge, hydrophobicity and cationic surfactants DTAB and TTAB on BLC at pH 7.4 and 9.4 which are two and four units above pI, respectively. We have used techniques like turbidity, Rayleigh light scattering, far-UV CD, ThT, ANS, Congo red binding assay, DLS, and transmission electron microscopy. The low concentration ranges of DTAB (0–600 μM) and TTAB (0–250 μM) were observed to increase aggregation at pH 9.4. Nevertheless, at pH 7.4 only TTAB was capable of inducing aggregate. DTAB did not produce any significant change in secondary structure at pH 7.4 suggestive of the role of respective charges on surfactants and protein according to the pI and alkyl chain length. The morphology of aggregates was further determined by TEM, which proved the existence of a fibrillar structure. The surfactants interaction with BLC was primarily electrostatic as examined by ITC. Our work demystifies the critical role of charge as well as hydrophobicity in amyloid formation.